2002
DOI: 10.1161/01.cir.0000020013.73106.d8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characterization of Patients With Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Background-Mutations in the cardiac ryanodine receptor gene (RyR2) underlie catecholaminergic polymorphic ventricular tachycardia (CPVT), an inherited arrhythmogenic disease occurring in the structurally intact heart. The proportion of patients with CPVT carrying RyR2 mutations is unknown, and the clinical features of RyR2-CPVT as compared with nongenotyped CPVT are undefined. Methods and Results-Patients with documented polymorphic ventricular arrhythmias occurring during physical or emotional stress with a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
861
2
32

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,048 publications
(913 citation statements)
references
References 21 publications
18
861
2
32
Order By: Relevance
“…Changes in cardiac function by the two steps coincided with changes in biomarkers including RyR2 and its modulator FKBP12.6, as well as SERCA2a and its modulator PLB. This is in line with other published findings on aggravating cardiac failure by ISO injection [5,[29][30][31] .…”
Section: Discussionsupporting
confidence: 93%
“…Changes in cardiac function by the two steps coincided with changes in biomarkers including RyR2 and its modulator FKBP12.6, as well as SERCA2a and its modulator PLB. This is in line with other published findings on aggravating cardiac failure by ISO injection [5,[29][30][31] .…”
Section: Discussionsupporting
confidence: 93%
“…Because the double mutant channel showed a negative shift of the steady-state inactivation curve and an increased proportion of Na channels that enter an intermediate state of inactivation, there is a reduction in cardiac Na current, which is characteristic of SCN5A mutations in those with symptomatic Brugada syndrome 18,28 . These results suggest that asymptomatic individuals with "functionally proven" SCN5A mutations with loss-of-function properties should be carefully followed to avoid lethal events as was observed in the SUNDS 29 as well as in long-QT syndrome 30 . We previously found an SCN5A mutation R367H in a family with atrial standstill complicated with J wave elevation in the inferior leads 22 , while Hong et al found the same mutation in a typical Brugada syndrome family 31 .…”
Section: Genetic Analysis Of the Case #2mentioning
confidence: 83%
“…Exercise tests are often used in the diagnosis and monitoring of therapy in CPVT, however mutation carriers may display no features during testing [4]. As in our family, there are reports of symptomatic RYR2 mutation carriers who have inherited the pathogenic mutation from completely asymptomatic parents [5]. Clinical assessment is limited in the evaluation of at-risk individuals and therefore cascade genetic testing is a more sensitive and specific way of screening in families with CPVT.…”
Section: Discussionmentioning
confidence: 97%
“…The incomplete penetrance of the condition can make it difficult to identify at-risk individuals, hence molecular genetic testing can be of particular value [5]. We describe a large family with a history of sudden death highlighting the value and clinical utility of molecular genetic testing for CPVT.…”
Section: Introductionmentioning
confidence: 99%